The Effect of Corporate Social Responsibility Information Disclosure on Total Factor Productivity - Liu, Yichen (Asia Pacific Economic and Management Review, 2025)
This study examines the impact mechanism of corporate social responsibility (CSR) information disclosure quality on total factor productivity (TFP) using data from Chinese A-share listed companies during 2010–2023. Employing a dual-pathway framework of resource aggregation and supervisory governance, we measure TFP via the LP and OP methods and analyze 39,844 firm-year observations through a mediation effect model. Results indicate that CSR disclosure quality significantly enhances firm-level TFP, with amplified effects in state-owned enterprises and firms audited by the Big Four. Mechanism tests demonstrate that CSR disclosure operates through four channels: alleviating financing constraints, optimizing human capital structure, intensifying media attention, and improving internal control quality. By integrating TFP into the analytical framework of CSR economic consequences, this research extends stakeholder and signaling theories, elucidating the micro-mechanisms through which sustainable development practices affect productivity. The conclusions provide empirical evidence for enterprises to optimize CSR strategies for productivity gains and for policymakers to refine disclosure regulatory systems, with implications for fostering high-quality development.